2020
DOI: 10.1504/ijitst.2020.104574
|View full text |Cite
|
Sign up to set email alerts
|

A new model for communities' detection in dynamic social networks inspired from human families

Abstract: Nowadays, social networks have been widely used by different people for different purposes in the world. The discovering of communities is a widespread subject in the space of social networks analysis. Many interesting solutions have been proposed in the literature. However, most solutions have common problems: the stability and the community structures quality. In this paper, we propose a new model to find communities based on a new concept called 'large families'. This model will be used, to motivate a commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This definition was extended to include "any recommender system that targets social media domains" [26]. The new definition covers systems recommending any objects in social media domains such as items, tags, links, people, and communities [17,57]. It has been shown that social considerations improve recommender systems since there is a significant overlap between users' interest and connections [48,56,61].…”
Section: Recommender Systemsmentioning
confidence: 99%
“…This definition was extended to include "any recommender system that targets social media domains" [26]. The new definition covers systems recommending any objects in social media domains such as items, tags, links, people, and communities [17,57]. It has been shown that social considerations improve recommender systems since there is a significant overlap between users' interest and connections [48,56,61].…”
Section: Recommender Systemsmentioning
confidence: 99%
“…NICE [9] uses hierarchical clustering techniques to build overlay tree, whereby group members arrange themselves into clusters with the neighboring nodes. Recent type of ALM based applications have been emerged the P2P networking such as streaming [14], telemedecine [15] and social networking [16]. The main objective of our proposed model is to build an efficient and optimized multicast tree from any node (root or sender) to all other nodes (receivers) using HPM as underlying architecture.…”
Section: Application Layer Multicastmentioning
confidence: 99%